The Effect of Capital Structure ana Digital Transformation on the Financial Performance of MSMEs with Government Policy as a Moderating Variable - Octaviana Ardaniswara; Puji Endah Purnamasari (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to examine how capital structure and digital transformation influence the financial performance of Micro, Small, and Medium Enterprises (MSMEs), with government policy positioned as a moderating variable. The research subjects were MSMEs in the culinary sector operating in Lowokwaru District, Malang City, with a population of 2,786 businesses. A sample of 350 MSME owners was obtained using the Slovin formula and selected using a purposive sampling technique. Data were collected through a structured questionnaire and analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) approach. The results indicate that capital structure and digital transformation have a positive influence on MSME financial performance. Conversely, government policy was found to have neither a direct influence nor a moderating role in the relationship between the independent variables and financial performance. These findings confirm that MSME financial performance relies more on the internal capabilities of managers in optimizing capital use and utilizing digital echnology, rather than external government support. The novelty of this research lies in the integration of three theoretical foundations Modigliani Miller, Technology Acceptance Model (TAM), and Institutional Theory into a single analytical framework to assess both internal and external factors influencing the financial performance of MSMEs. This research contributes to the development of management science by providing empirical evidence that an effective capital structure and the adoption of digital technology play a strategic role in the financial sustainability of MSMEs. This research also emphasizes the need for more adaptive, accessible, and targeted government policies to improve digital readiness and support the growth of culinary MSMEs.